2015
DOI: 10.1590/1516-1439.028715
|View full text |Cite
|
Sign up to set email alerts
|

Fresh-state Properties of Self-compacting Mortar and Concrete with Combined Use of Limestone Filler and Fly Ash

Abstract: This paper presents the results of a study on the behaviour of self-compacting concrete (SCC) in the fresh and hardened states, produced with binary and ternary mixes of fly ash (FA) and limestone filler (LF), using the method proposed by Nepomuceno. His method determines the SCC composition parameters in the mortar phase (self-compacting mortar -SCM) easily and efficiently, whilst guaranteeing the SCC properties in both the fresh and hardened states. For this, 11 SCMs were studied: one with cement (C) only; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…FA mixes among all binary and ternary SCMs mixes show the worst compressive strength performance. In the literature, many authors have reported that replacement of FA slows down hardening at early age . It was also stated that calcium in the FA behaves as a pollutant, reduce the mechanical strength and form hydrate assemblages that slow the reaction rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FA mixes among all binary and ternary SCMs mixes show the worst compressive strength performance. In the literature, many authors have reported that replacement of FA slows down hardening at early age . It was also stated that calcium in the FA behaves as a pollutant, reduce the mechanical strength and form hydrate assemblages that slow the reaction rate.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, many authors have reported that replacement of FA slows down hardening at early age. 17,37,38 It was also stated that calcium in the FA behaves as a pollutant, reduce the mechanical strength and form hydrate assemblages that slow the reaction rate 39 . It can be seen that FA causes significant declines in compressive strength aged 28 days compared to control mix but at 180 days similar strength performance can be observed at FA content of 5-15%.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…As found out by various authors [13,[27][28][29][30][31], the mixing procedure has a significant influence on the self-compacting mortars fresh-state properties, namely on the optimization of the use of superplasticizers. They confirmed that the mixing time until the superplasticizer is added is not irrelevant to its efficiency and consequently it alters the self-compatibility conditions of these mortars.…”
Section: Mortar Mixture Proceduresmentioning
confidence: 99%
“…However, it is stressed that the objective in terms of spread and mini V-funnel test results was simply to comply with the workability parameters defined in the reference documents [13,[27][28][29][30][31], in order to reach self-compatibility, which was successfully done for all the mixes produced. Table 4 and Fig.…”
Section: Fresh-state Propertiesmentioning
confidence: 99%
“…The main difference between SCC, with or without RA, and conventional concrete (CC) is their workability characteristics that allow them to completely fill the moulds, even in densely reinforced elements, with no flocculation, exudation or segregation, solely under their own weight and with no resort to compaction methods (Silva and de Brito, 2015).…”
Section: Introductionmentioning
confidence: 99%